Microcredit and Sustainable School Improvement in Port Harcourt Metropolis, Nigeria - Olatokunbo, Olarewaju (American Journal of Education and Practice, 2023)
Purpose: This study examined the relationship between microcredit and sustainable school improvement in Port Harcourt Metropolis, Nigeria. Methodology: The study adopted the cross-sectional research survey design. Primary data was generated through structured questionnaire. Therefore, the population of the study is 918 schools. A sample Size of 279 Proprietors, Administrators and Principals was determined using the Taro Yeman's Sample Size Formula.The reliability of the instrument was achieved by the use of the Cronbach Alpha Coefficient with all the items scoring above 0.70. The hypotheses were tested using the Spearman's Rank Order Correlation Coefficient. The tests were carried out at a 0.05 significance level. Findings: The findings of the study indicate a positive and significant relationship between microcredit and sustainable school improvement in Port Harcourt Metropolis, Nigeria. The study concludes that the availability of microcredit facilities has played a vital role in promoting the sustainability of schools in the region. Recommendations: Therefore, the study recommends that Government agencies, financial institutions, and non-governmental organizations should collaborate to expand access to microcredit facilities specifically tailored for educational institutions. This will enable more schools in Port Harcourt Metropolis to benefit from the positive effects of microcredit on sustainability.